2019
DOI: 10.1016/j.esxm.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

What Patients and Partners Want in Interventions That Support Sexual Recovery After Prostate Cancer Treatment: An Exploratory Convergent Mixed Methods Study

Abstract: Introduction Men treated for prostate cancer suffer from treatment-related sexual side effects that adversely affect their relationships and quality of life. Aim To investigate what prostate cancer survivors and their partners want from a sexual recovery intervention, and whether they consider an online tool acceptable for use in promoting sexual recovery. Methods This mixed-methods study included focus groups and interviews with both heteros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 37 publications
3
58
0
Order By: Relevance
“…The extent to which the participants agreed that they were comfortable when discussing sexual issues also did not change, but these scores were relatively high at baseline. This supports the findings from studies that have found that the level of comfort in men with prostate cancer is not a significant barrier to discussing sexual issues [ 21 , 48 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The extent to which the participants agreed that they were comfortable when discussing sexual issues also did not change, but these scores were relatively high at baseline. This supports the findings from studies that have found that the level of comfort in men with prostate cancer is not a significant barrier to discussing sexual issues [ 21 , 48 ].…”
Section: Discussionsupporting
confidence: 87%
“…Despite these recommendations, the information provided varies greatly and is not routinely available across services [ 9 ]. Patients and their partners frequently report that they do not receive adequate support to manage these concerns [ 21 , 22 ]. In a study of prostate cancer follow-up at urology and radiotherapy clinics, the sexual aspects of recovery were not discussed in 46% and 48%, respectively, of the observed consultations [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cancer reported to prefer their partners to be involved in communication regarding sexuality and intimacy and sexual recovery with a healthcare professional, and so do their partners (Mehta et al, 2019). In accordance with our study, in current medical practice, a discussion about sexuality and intimacy with a healthcare professional does not take place for most cancer patients and partners.…”
Section: Discussionsupporting
confidence: 83%
“…Current findings suggest that partners of patients with cancer are in need of practical advice regarding sexuality and intimacy and experiences from others. Suitable information with respect to sexuality and intimacy for partners can be helpful to prepare partners for sexual side effects and create realistic expectations about sexual function after cancer (Mehta et al, 2019). Lack of knowledge regarding sexual side effects can lead to unmet sexual needs, which can negatively influence quality of life and may result in lower levels of relationship satisfaction (Acquati et al, 2018;Dobinson et al, 2016;Park & Hwang 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation